Modernists' Opinion on the Oriental Grammatical View: Khadija Al-Hadith, Ibrahim al-Samarrai and Ali Abu al-Makarim as examples - Nimea, Firdous Talb (Al-Adab Journal, 2021)
The recent oriental studies significantly influence researchers and scholars who study various Arabic language subfields, including grammatical studies. This has led to forming new views and understanding which can harmonically correspond with new scientific findings and defend the Arabic Heritage from orientalists’ attempts to dismantle the nation it’s language, the language of the Holy Quran.In this research study, we compare three different directions in Arabic grammatical study. The first direction tends to fanatically support the old grammatical views, Khadija Al-Hadithi represents this direction. The second direction is influenced by the orientalists’ views, which is represented by Ibrahim al-Samarrai. The third one is Ali Abu al-Makarim’ direction, who formed a new methodology to study Arabic grammar. I believe that the three scholars (researchers) form the Arabic grammatical modern views on the impacts of orientalism.In this article, three research areas are discussed: (1) their opinion on the Arabic grammar directions, (2) their views on the origin of Arabic grammar (Hearing and Measurement) and (3) facilitating Arabic grammar, in their views.One of the key results obtained, in this paper, is that orientalism has no obvious influence on Khadija Al-Hadithi and Abu Al-Makarim, unlike Ibrahim Al-Samarrai.